Deposition-dependent morphology and infrared vibrational spectra of brominated tetraazaperopyrene layers - Tzschoppe, Michael; Huck, Christian; Günther, Benjamin; Matthiesen, Maik; Rohnacher, Valentina; Gade, Lutz H.; Zaumseil, Jana; Pucci, Annemarie (The journal of physical chemistry. C, Energy, materials, and catalysis, 2020)
A detailed infrared spectroscopic characterization - supported by atomic force microscopy - of core brominated tetraazaperopyrene (TAPP-Br) layers in terms of molecular orientation and stability against electron irradiation is presented. The anisotropy and the average molecular orientation of TAPP-Br molecules in optoelectronic device-relevant thin films (with ca. 20 nm thickness), grown by thermal evaporation under ultrahigh vacuum conditions and in a zone-cast sample, were established. To this end, the tensor components of the dielectric function were determined on the basis of spectra of a pellet sample and of a variety of polarization-dependent spectra of layers. Supported by density functional theory, the experimentally derived tensor components were related to dipoles of selected vibrational modes in the anisotropic TAPP-Br molecule and so to the average molecular orientation in the polycrystalline layers. Additionally, electron beam damage for energies ranging from ten to hundreds of electron volts was studied in order to obtain the threshold energy below which scanning electron microscopy can be carried out in a nondestructive way.